Grade retention in Spain: the right way? - López-Agudo, Luis Alejandro; Prieto-Latorre, Claudia; Marcenaro-Gutiérrez, Óscar David (Springer Heidelberg, 2023)
There is a wide debate on the convenience of grade retention for students’ future cognitive development. Nevertheless, due to the endogenous characteristics of grade retention to explain students’ academic performance, most of the literature fails in capturing its actual influence. In the present research we intend to get as close as possible to the causal effect of grade retention on lower secondary education students’ academic competences. In order to do this, we employ rich administrative census and longitudinal data from the most populated region of Spain (Andalusia) using Ordinary Least Squares (OLS) estimation method with student fixed-effects within-students between-academic years. Our results show a positive influence of grade retention on students’ academic competences in the short-term in mathematics, but a null one in reading.
Keywords: Rendimiento académico; Fracaso escolar; Enseñanza secundaria; Grade retention; Student fixed-effects; Lower secondary education; Reading; Mathematics